2013
DOI: 10.1080/02678292.2013.786795
|View full text |Cite
|
Sign up to set email alerts
|

High-transmittance polymer-stabilised blue-phase liquid crystal display with double-sided protrusion electrodes

Abstract: A polymer-stabilised blue-phase liquid crystal display (PSBP-LCD) with double-sided protrusion (DSP) electrodes structure is proposed. The oblique electric field between the protrusion electrodes inside both top and bottom glass substrates can induce more isotropic-to-anisotropic transition in the polymer-stabilised blue-phase liquid crystal (PS-BPLC) medium through Kerr effect than using the in-plane switching electrode. For the same electrode width, spacing and cell gap, the transmittance of PSBP-LCD with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…One of the major challenges is reducing the voltage V m [100][101][102][103][104][105][106][107] below 10 V, thereby enabling electric addressing with thin film transistors. In addition, it is important to lower the hysteresis ΔV [108][109][110][111][112][113][114][115][116][117][118][119][120][121] in order to achieve reproducible gray levels. A large optical contrast between the bright and the dark state is only possible if no non-zero intensity I 0,2 caused by residual birefringence [122] appears after removing the voltage.…”
Section: Kerr Effect In Polymer-stabilized Blue Phases: Recent Develomentioning
confidence: 99%
“…One of the major challenges is reducing the voltage V m [100][101][102][103][104][105][106][107] below 10 V, thereby enabling electric addressing with thin film transistors. In addition, it is important to lower the hysteresis ΔV [108][109][110][111][112][113][114][115][116][117][118][119][120][121] in order to achieve reproducible gray levels. A large optical contrast between the bright and the dark state is only possible if no non-zero intensity I 0,2 caused by residual birefringence [122] appears after removing the voltage.…”
Section: Kerr Effect In Polymer-stabilized Blue Phases: Recent Develomentioning
confidence: 99%
“…These interactions depend upon the nature of polymeric chain, the properties of the LC medium and LC ordering on the surface of polymeric layer. Very recently, modified LC materials have been applied [9][10][11] in display industry for achieving better performance of devices. Su et al [9] have shown that the transmittance of the polymer-stabilised blue-phase liquid crystal display with double-sided protrusion is 29% higher than that using the IPS electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, modified LC materials have been applied [9][10][11] in display industry for achieving better performance of devices. Su et al [9] have shown that the transmittance of the polymer-stabilised blue-phase liquid crystal display with double-sided protrusion is 29% higher than that using the IPS electrodes. Zhang et al [10] observed unique optical features in a cholesteric liquid crystal with helically aligned molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode shapes, cell gaps ( d ), electrode widths ( w ), and electrode gaps ( l ) will affect the transmittance of LSP and RSP. In our simulation, we adopt the protrusion electrode . The electrode width w = 5 μ m, the electrode gap l = 3 μ m, and the cell gap d = 3 μ m. And the taper angle is 30 °, which means the height of protrusion electrode is h = 1.4 μ m. This patterned electrode structure has the feature of high transmittance and low light leakage.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…In our simulation, we adopt the protrusion electrode. 13,14 The electrode width w = 5 μm, the electrode gap l = 3 μm, and the cell gap d = 3 μm. And the taper angle is 30°, which means the height of protrusion electrode is h = 1.4 μm.…”
Section: Simulations and Resultsmentioning
confidence: 99%